Chronic constipation in adults: Contemporary perspectives and clinical challenges. 2: Conservative, behavioural, medical and surgical treatment. Issue 7 (1st February 2021) - Corsetti, Maura; Brown, Steven; Chiarioni, Giuseppe; Dimidi, Eirini; Dudding, Thomas; Emmanuel, Anton; Fox, Mark; Ford, Alexander C.; Giordano, Pasquale; Grossi, Ugo; Henderson, Michelle; Knowles, Charles H.; et al.
Abstract: Background: Chronic constipation is a prevalent disorder that affects quality of life of patients and consumes resources in healthcare systems worldwide. In clinical practice, it is still considered a challenge as clinicians frequently are unsure as to which treatments to use and when. Over a decade ago, a Neurogastroenterology and Motility journal supplement devoted to the investigation and management of constipation was published ( Neurogastroenterol Motil 2009;21(Suppl 2):1). In October 2018, the 3rd London Masterclass, entitled "Contemporary management of constipation" was held. The faculty members of this symposium were invited to write two reviews to present a collective synthesis of talks presented and discussions held during this meeting. The first review addresses epidemiology, diagnosis, clinical associations, pathophysiology, and investigation. Purpose: The present is the second of these reviews, providing contemporary perspectives and clinical challenges regarding behavioral, conservative, medical, and surgical treatments for patients presenting with constipation. It includes a management algorithm to guide clinical practice.